Orthogonal polynomials : 2nd AIMS-Volkswagen Stiftung Workshop, Douala, Cameroon, 5-12 October 2018 /: 2nd AIMS-Volkswagen Stiftung Workshop, Douala, Cameroon, 5-12 October 2018. ([2020]) - Foupouagnigni, Mama; Koepf, Wolfram
No abstract available